2017
DOI: 10.3126/bjhs.v2i2.18520
|View full text |Cite
|
Sign up to set email alerts
|

Granisetron and Ondansetron on Post Operative Nausea and Vomiting in Laparoscopic Cholecystectomy Under General Anesthesia At Bir Hospital Kathmandu, Nepal

Abstract: IntroductionLaparoscopic cholecystectomy has higher incidence of postoperative nausea and vomiting (PONV). In routine practice single dose of drug is given prophylactically during the surgery.ObjectiveThis study aimed to compare the antiemetic efficacy of two different 5-hydroxytryptamine-3 (5HT3) receptor antagonists, Ondansetron and Granisetron when given prophylactically to patients undergoing laparoscopic cholecystectomy.MethodologyIt was a randomized, single blind study, conducted in 75 patients undergoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
(5 reference statements)
1
2
0
Order By: Relevance
“…In the study done by Ommid et al, incidence of PONV was 29% 18 and that in study by Bhattarai et al was 26%. 10 The results were similar to this study. Study done by Bhattacharya et al found the incidence of PONV in Granisetron group to be 7%.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the study done by Ommid et al, incidence of PONV was 29% 18 and that in study by Bhattarai et al was 26%. 10 The results were similar to this study. Study done by Bhattacharya et al found the incidence of PONV in Granisetron group to be 7%.…”
Section: Discussionsupporting
confidence: 89%
“…Similar incidence was found in study done by Bhattarai et al (54%) and Ommid et al (52%). 10,18 Study done by Bhattacharya et al found the incidence of PONV in Ondansetron group was 10%. 19 This difference in incidence in PONV might be because they conducted study in day care gynaecological laparoscopy and shorter duration of surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation